(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The need to study the problem of motives in children aged 7-10, an important component of the personal development of a primary school student, is substantiated by the method of comparative-logical analysis. The article provides scientific information on the need to provide optimal conditions for the development of a young person, the manifestation of his abilities and the realization of his potential as a bright personality, the harmonious combination of personal interest in a particular type of activity and a free, creative attitude to life.